PENGARUH PENGETAHUAN RIBA TERHADAP PERILAKU UTANG PIUTANG PADA ANGGOTA KOPERASI WANITA RUKUN LESTARI DESA DERO KECAMATAN BRINGIN KABUPATEN NGAWI - Siti Maysaroh; Linawati Linawati (Commodity : Jurnal Perbankan dan Keuangan Islam, 2022)
Islam is a universal religion that regulates everything perfectly. The Qur'anregulates how to meet all needs in daily life, and how to transact with otherpeople in a sharia way, such as doing debt transactions. So knowledge of Ribamembers is very important to make them aware of the impacts and dangers ofRiba. This study aims to find out how knowledgeable Kopwan members areabout usury knowledge, whether Kopwan members have carried out sharia debtand credit, and whether or not usury knowledge influences debt and creditbehavior among members of the Rukun Lestari Women's Cooperative, DeroVillage, Bringin District, Ngawi Regency. This study uses a type of quantitativeresearch. While collecting data using observation, questionnaires, anddocumentation. To find out how much influence the x variable has on the yvariable, this study uses hypothesis testing analysis using t-test statistical dataanalysis. After being researched and analyzed, the researcher can then concludethat: public knowledge about riba is still low.